Modern Methods in New Testament Philology - Angus, Samuel (Harvard theological review, 1909)
The language of the Greek New Testament has been under the continual search-light of criticism since the early part of the seventeenth century, when the keen debate between the Purist and the Hebraist produced a copious literature. The former laid a very heavy burden on his own shoulders. Although he could easily argue for his thesis of the “purity” of the New Testament language by citing numberless parallels between it and the best Greek writers, it was hard to account for the many points of divergence, and consequently the Hebraist steadily gained ground. Antecedent probability, as well as common sense, seemed to be on the side of the latter. For the New Testament was akin to the Septuagint, and that was regarded as a treasure-house of Semitisms. Moreover most of the writers of the New Testament were Jews, and nothing seemed more natural than that their Greek should be deeply tinged with the idioms of their native tongue. Accordingly Hebraism was granted large concessions, and under it were included not only the Greek expressions which happened to have sister-constructions in Hebrew or Aramaic, but also many usages peculiar to Greek but unusual in the days of the best Attic. These Semitisms were supposed so to affect syntax, vocabulary, and style as to make the result un-greek.